2009
DOI: 10.1615/atomizspr.v19.i6.30
|View full text |Cite
|
Sign up to set email alerts
|

Spray Structure From Double Fuel Injection in Multihole Injectors for Gasoline Direct-Injection Engines

Abstract: Citation: Mitroglou, N., Nouri, J. M. & Arcoumanis, C. (2009). Spray structure from double fuel injection in multihole injectors for gasoline direct-injection engines. Atomization and Sprays, 19(6), pp. 529-545. doi: 10.1615/AtomizSpr.v19.i6.30 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent ABSTRACTThe spray characteristics of double fuel injection in multi-hole injectors for direct-injection gasoline engines have been ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Goddwin et al 5 showed axial droplet velocities of around 80 m/s for a 5 MPa gasoline spray from a swirl injector in the near-nozzle region. For higher injection pressures and multi-hole injectors, Mitroglou 6 shows mean velocities of around 110 m/s for 8 MPa injection pressure and 150 m/s for 12 MPa injection pressure at 2.5 mm nozzle distance.…”
Section: Analysis Of Flow Conditions In Gdi Spraysmentioning
confidence: 98%
“…Goddwin et al 5 showed axial droplet velocities of around 80 m/s for a 5 MPa gasoline spray from a swirl injector in the near-nozzle region. For higher injection pressures and multi-hole injectors, Mitroglou 6 shows mean velocities of around 110 m/s for 8 MPa injection pressure and 150 m/s for 12 MPa injection pressure at 2.5 mm nozzle distance.…”
Section: Analysis Of Flow Conditions In Gdi Spraysmentioning
confidence: 98%
“…Knowledge of the internal nozzle geometry for real spray equipment is therefore necessary to relate these features to external spray characteristics and to facilitate predictive simulation. Furthermore, for transient sprays-particularly for the multi-pulse injection strategies [24, [195][196][197] that are increasingly common in automotive applications-the geometry changes rapidly as the needle moves within the injector. Indeed, small quantity injections can be composed entirely of the transients associated with opening and closing of the injector.…”
Section: Upstream Internal Nozzle Flow Regionmentioning
confidence: 99%
“…It also has the flexibility to direct spray plumes at desired locations to help meet the combustion system requirements. 2…”
Section: Introductionmentioning
confidence: 99%